Inversor meia-ponte com estrutura de conversores CC-CC bipolares com baixa corrente de fuga - Vendruscolo, Miréli Binder (2023)
The objective of this dissertation is to develop a transformerless photovoltaic inverter that eliminates leakage current. The system consists of two stages: a non-isolated DC-DC converter, which features a bipolar output, and a DC-AC converter. Within the scope of the first DC-DC stage, two configurations were proposed: the bipolar Boost converter with two active switches, with a comparative analysis between synchronous and phase shift modulation, as well as the bipolar Boost converter with a single active switch. The second stage consists of a half-bridge DC-AC converter. Due to the elimination of galvanic isolation, it is necessary to ground the metal frame of the photovoltaic modules for safety reasons, which leads to the formation of parasitic capacitance between the photovoltaic cells and the ground. Depending on the modulation and topology of the inverter used, voltage fluctuations may occur in these parasitic capacitances, generating leakage currents that flow through the inverter circuit and are injected into the power grid. These leakage currents affect the safety, electromagnetic compatibility, and harmonic content of the power injected into the power grid. However, despite the difficulties, the interest in transformerless inverters is justified by the advantages such as higher efficiency, lower weight, smaller volume and lower cost. On this basis, the objective is achieved by grounding the photovoltaic module to the power grid and using a DC-DC converter with bipolar outputs as the first stage, followed by a DC-AC half-bridge converter as the second stage. This configuration results in the midpoint of the DC bus capacitors being grounded and producing a constant common mode voltage. Therefore, this dissertation contributes to the development of an inverter with classical topologies, featuring high efficiency, simple design and low leakage current. Throughout the work, a detailed theoretical analysis of the inverter operation is performed. Moreover, an experimental prototype is implemented to verify the performance by evaluating the waveforms, the efficiency of each DC-DC and DC-AC inverter, the leakage current and the connection to the electrical grid. The experimental results confirm the previously mentioned characteristics and support the theoretical analysis of the inverter operation.